Environmental Education Through Eco-Literacy: Integrating Sustainability into English Language Teaching - Kazazoglu, Semin (MDPI, 2025)
Eco-literacy, the ability to understand and apply ecological knowledge to foster sustainable living, is increasingly recognized as an essential educational objective. Traditionally linked to disciplines such as science and social studies, eco-literacy is now gaining traction in English language teaching (ELT) to align language instruction with global sustainability goals. While previous research has highlighted the importance of sustainability in education, there is a scarcity of studies on how eco-literacy can be effectively integrated into language learning. To address this gap, this study aims to explore ELT students' perceptions of the impact of eco-literacy-focused writing activities on their language development and awareness of environmental issues. Employing a mixed-methods design, data were collected through pre-and post-tests on changes in students' perceptions of eco-literacy-focused writing activities. Semi-structured interviews with a subset of participants offered qualitative insights into their experiences. The findings revealed significant changes in students' perceptions, particularly in their understanding of environmental vocabulary and critical thinking related to eco-literacy. Writing tasks and discussions on ecological themes enhanced their engagement and understanding of global sustainability issues. However, challenges such as limited prior knowledge of environmental topics and the need for further training were identified. This study contributes to the growing body of literature on sustainable language education by demonstrating the pivotal role of integrating eco-literacy into ELT classrooms. It also provides practical recommendations for teacher training programs to develop pedagogical strategies promoting linguistic and environmental learning outcomes, ultimately preparing educators to address global issues in diverse teaching contexts.
Keywords: sustainable language learning; environmental education; eco-literacy; descriptive writing; English language teaching; Science & Technology - Other Topics; Environmental Sciences & Ecology